Impact of Clinical Pharmacist-led Interventions in Turkey - SANCAR, MESUT (TURKISH PHARMACISTS ASSOC, 2021)
Detecting drug-related problems (DRPs) is important in pharmaceutical care in for better therapeutic outcomes. Clinical pharmacists-led comprehensive medication management plays a crucial role in the rational use of drugs by preventing, identifying, and resolving DRPs. In this review, we aimed to determine the effect of interventions on patient outcomes performed by clinical pharmacists in Turkey. A systematic literature search was performed on PubMed, Google Scholar, EMBASE, Cochrane Library, and Turkish databases (ULAKBIM, Dergipark). The main categories were clinical pharmacist, intervention, and Turkey. Two reviewers reviewed each article independently. Two independent reviewers screened all records and extracted data

disagreements were resolved through a consensus. Randomized controlled studies, pre- to post-intervention comparison studies, and cross-sectional studies including pharmacist-led interventions were included in the review. This review included 15 articles evaluating clinical pharmacist interventions. Ten studies (66.7%) focused on DRPs and pharmacist interventions to these problems, while the remaining 5 (33.3%) studies focused on patient education and adherence issues. Studies were conducted in oncology (33.3%), geriatrics (20.0%), chest diseases (13.3%), psychiatry (6.7%), cardiology (6.7%), and infectious diseases (6.7%) clinics. When results of studies are reviewed, most of the interventions were made at the prescriber level followed by the drug level and patient level. Problems were solved in 54.2-93.2% of DRPs, and adherence, patient knowledge, or skills were improved in most of the studies. Most of the studies were carried out within the scope of a postgraduate or doctorate thesis and yet various positive outcomes such as the prevention of side effects, increased quality of life, and decreased duration of hospital stay were observed with high positive rates of interventions, which indicate that other healthcare workers are ready to collaborate with the clinical pharmacists in Turkey.
Keywords: Clinical pharmacy; drug-related problems; pharmaceutical care; clinical pharmacist; Turkey; DRUG-RELATED PROBLEMS; PHARMACEUTICAL CARE PROGRAM; SERVICES; EDUCATION; RISK